Papular xanthoma in a 17-month-old girl. - Ingravallo, G. (European Journal of Pediatric Dermatology, 2022)
Papular xanthoma belongs to Class II - non-Langerhans histiocytosis with dermal dendrocytes - along with juvenile xanthogranuloma and other less frequent forms (3). Papular xanthoma mainly affects the child (1, 2), but it can also affect the adult (5). Our case adheres to the criteria proposed by Winkelmann (5) for papular xanthoma, i.e. 1- asymptomatic papules distributed throughout the skin, 2- absence of visceral involvement, 3- normal lipid profile, 4- infiltrate composed mainly of foam cells, 5- absence of one initial histiocytic phase and inflammatory infiltrate. From a clinical point of view (2) the lesions appear in the first year of life in a progressive way for some months, mainly affecting the back and face, always sparing the palmar-plantar region and mucous membranes; their number varies, but they can usually be counted, and their diameter is also variable, the smallest being of 1 mm, the largest rarely exceeding 1 cm. These are yellow lesions from their appearance, which spontaneously regress in months, sometimes years (4). Mucous membranes and internal organs are always spared and the lipid profile is normal. (...).